Intramuscular mRNA BNT162b2 vaccine against SARS-CoV-2 induces neutralizing salivary IgA - Stolovich-Rain, Miri; Kumari, Sujata; Friedman, Ahuva; Kirillov, Saveliy; Socol, Yakov; Billan, Maria; Pal, Ritesh Ranjan; Das, Kathakali; Golding, Peretz; Oiknine-Djian, Esther; Sirhan, Salim; Sagie, Michal Bejerano; et al. (Frontiers in Immunology, 2023)
Intramuscularly administered vaccines stimulate robust serum neutralizing antibodies, yet they are often less competent in eliciting sustainable ‘sterilizing immunity’ at the mucosal level. Our study uncovers strong temporary neutralizing mucosal component, emanating from intramuscular administration of an mRNA vaccine. We show that saliva of BNT162b2 vaccinees contains temporary IgA targeting the Receptor-Binding-Domain (RBD) of SARS-CoV-2 spike protein and demonstrate that these IgAs mediate neutralization. RBD-targeting IgAs were found to associate with the Secretory Component, indicating their bona-fide transcytotic origin and their dimeric tetravalent nature. The mechanistic understanding of the high neutralizing activity provided by mucosal IgA, acting at the first line of defence, will advance vaccination design and surveillance principles, pointing to novel treatment approaches, and to new routes of vaccine administration and boosting.